Tom de Jong, 28 January 2021
(Following Bezem, Buchholtz, Grayson and Shulman)

We construct the circle 𝕊¹ as the type of ℤ-torsors, following "Construction of
the circle in UniMath" by Bezem, Buchholtz, Grayson and Shulman
(doi:10.1016/j.jpaa.2021.106687). The construction needs univalence of 𝓤₀,
propositional truncations and function extensionality for every two universes.

Rather than proving the induction principle directly as in "Construction of the
circle in UniMath", we prove the induction principle abstractly from the
universal property.

\begin{code}

{-# OPTIONS --safe --without-K #-}

open import MLTT.Spartan

open import UF.Base
open import UF.Equiv hiding (_≅_)
open import UF.Equiv-FunExt
open import UF.EquivalenceExamples
open import UF.FunExt
open import UF.Lower-FunExt
open import UF.PropTrunc
open import UF.SIP
open import UF.Sets
open import UF.Sets-Properties
open import UF.Subsingletons
open import UF.Subsingletons-FunExt
open import UF.UA-FunExt
open import UF.Univalence

open import Circle.Integers
open import Circle.Integers-Properties
open import Circle.Integers-SymmetricInduction

module Circle.Construction
        (pt : propositional-truncations-exist)
        (ua : is-univalent 𝓤₀)
       where

fe₀ : funext 𝓤₀ 𝓤₀
fe₀ = univalence-gives-funext ua

open PropositionalTruncation pt
open sip
open sip-with-axioms

\end{code}

The pointed type of ℤ-torsors base : Tℤ. This type is connected (like 𝕊¹) almost
by definition.

\begin{code}

Tℤ : 𝓤₁ ̇
Tℤ = Σ X  𝓤₀ ̇ , Σ f  (X  X) ,  ( , succ-ℤ)  (X , f) 

base : Tℤ
base = ( , succ-ℤ ,  refl )

Tℤ-is-connected : (X Y : Tℤ)   X  Y 
Tℤ-is-connected (X , f , p) (Y , g , q) = ∥∥-rec ∥∥-is-prop ϕ p
 where
  ϕ : ( , succ-ℤ)  (X , f)
      X , f , p  Y , g , q 
  ϕ refl = ∥∥-rec ∥∥-is-prop ψ q
   where
    ψ : ( , succ-ℤ)  (Y , g)
         , succ-ℤ , p  Y , g , q 
    ψ refl =  ap  Σ-assoc  (to-subtype-=  _  ∥∥-is-prop) refl) 

\end{code}

Next, we wish to define loop : base = base. To this end, we first characterize
equality of ℤ-torsors, for which we use the Structure Identity Principle.

\begin{code}

_≅_ : Tℤ  Tℤ  𝓤₀ ̇
(X , f , _)  (Y , g , _) = Σ e  (X  Y) , is-equiv e
                                          × (e  f  g  e)

Tℤ-structure : 𝓤₀ ̇  𝓤₀ ̇
Tℤ-structure X = X  X

Tℤ⁻ : 𝓤₁ ̇
Tℤ⁻ = Σ X  𝓤₀ ̇ , Tℤ-structure X

sns-data : SNS Tℤ-structure 𝓤₀
sns-data = (ι , ρ , θ)
 where
  ι : (X Y : Tℤ⁻)   X    Y   𝓤₀ ̇
  ι (X , f) (Y , g) (e , _) = e  f  g  e
  ρ : (X : Tℤ⁻)  ι X X (≃-refl  X )
  ρ (X , f) = refl
  h : {X : 𝓤₀ ̇ } {f g : Tℤ-structure X}
     canonical-map ι ρ f g  id {𝓤₀} {f  g}
  h refl = refl
  θ : {X : 𝓤₀ ̇ } (f g : Tℤ-structure X)
     is-equiv (canonical-map ι ρ f g)
  θ f g = equiv-closed-under-∼ _ _ (id-is-equiv (f  g)) h

characterization-of-Tℤ-= : (X Y : Tℤ)
                          (X  Y)  (X  Y)
characterization-of-Tℤ-= =
 characterization-of-=-with-axioms ua
  sns-data
   X f   ( , succ-ℤ)  (X , f) )
   X f  ∥∥-is-prop)

to-Tℤ-= : (X Y : Tℤ)  X  Y  X  Y
to-Tℤ-= X Y =  characterization-of-Tℤ-= X Y ⌝⁻¹

loop-≅ : base  base
loop-≅ = (succ-ℤ , succ-ℤ-is-equiv , refl)

loop : base  base
loop = to-Tℤ-= base base loop-≅

\end{code}

Another nice consequence of having characterized the equality of ℤ-torsors (and
the symmetric induction principle of ℤ) is that we can quickly prove that
(base = base) ≃ ℤ.

\begin{code}

loops-at-base-equivalent-to-ℤ : (base  base)  
loops-at-base-equivalent-to-ℤ =
 (base  base)                                            ≃⟨ I   
 (Σ e  (  ) , is-equiv e × (e  succ-ℤ  succ-ℤ  e)) ≃⟨ II  
 (Σ e  (  ) , is-equiv e × (e  succ-ℤ  succ-ℤ  e)) ≃⟨ III 
 (Σ e  (  ) , (e  succ-ℤ  succ-ℤ  e) × is-equiv e) ≃⟨ IV  
 (Σ e  (  ) , (e  succ-ℤ  succ-ℤ  e))              ≃⟨ V   
                                                         
  where
   I   = characterization-of-Tℤ-= base base
   II  = Σ-cong  e  ×-cong (≃-refl (is-equiv e))
                              (≃-funext fe₀ (e  succ-ℤ) (succ-ℤ  e)))
   III = Σ-cong  e  ×-comm)
   IV  = Σ-cong γ
    where
     γ : (e :   )
        (e  succ-ℤ  succ-ℤ  e) × is-equiv e
        (e  succ-ℤ  succ-ℤ  e)
     γ e = qinveq pr₁ (ϕ , η , ε)
      where
       ϕ : e  succ-ℤ  succ-ℤ  e
          (e  succ-ℤ  succ-ℤ  e) × is-equiv e
       ϕ c = (c , is-equiv-if-commute-with-succ-ℤ e c)
       η : ϕ  pr₁  id
       η (i , c) = to-subtype-=
                     _  being-equiv-is-prop' fe₀ fe₀ fe₀ fe₀ e) refl
       ε : pr₁  ϕ  id
       ε _ = refl
   V   = ℤ-symmetric-induction fe₀  _  )  _  succ-ℤ-≃)

⟨_⟩₂ : (X : Tℤ)   X    X 
 (X , f , t) ⟩₂ = f

_⁻ : Tℤ  Tℤ⁻
X  =  X  ,  X ⟩₂

Tℤ-=-from-Tℤ⁻-= : {X Y : Tℤ}  X   Y   X  Y
Tℤ-=-from-Tℤ⁻-= q = ap  Σ-assoc  (to-subtype-=  _  ∥∥-is-prop) q)

\end{code}

The connectedness of Tℤ gets us the following propositional induction principle,
which allows us to prove some further properties of ℤ-torsors. What's remarkable
(and in my opinion this is the crux of the paper by Bezem et al.) is that this
principle can be used to get the full recursion principle for Tℤ.

\begin{code}

Tℤ-prop-induction : {𝓤 : Universe} {P : Tℤ  𝓤 ̇ }
                   ((X : Tℤ)  is-prop (P X))
                   P base
                   (X : Tℤ)  P X
Tℤ-prop-induction {𝓤} {P} i p (X , f , t) = ∥∥-rec (i (X , f , t)) γ t
 where
  γ : ( , succ-ℤ)  (X , f)  P (X , f , t)
  γ q = transport P (Tℤ-=-from-Tℤ⁻-= q) p

⟨⟩-is-set : (X : Tℤ)  is-set  X 
⟨⟩-is-set = Tℤ-prop-induction  _  being-set-is-prop fe₀) ℤ-is-set

⟨⟩₂-is-equiv : (X : Tℤ)  is-equiv  X ⟩₂
⟨⟩₂-is-equiv = Tℤ-prop-induction
                 X  being-equiv-is-prop' fe₀ fe₀ fe₀ fe₀  X ⟩₂)
                succ-ℤ-is-equiv

⟨_⟩₂-≃ : (X : Tℤ)   X    X 
⟨_⟩₂-≃ X = ( X ⟩₂ , ⟨⟩₂-is-equiv X)

⟨_⟩₂⁻¹ : (X : Tℤ)   X    X 
⟨_⟩₂⁻¹ X =   X ⟩₂-≃ ⌝⁻¹

\end{code}

Next we derive the recursion principle following Bezem et al.

\begin{code}

module Tℤ-rec
        {A : 𝓤 ̇ }
        (fe : funext 𝓤 𝓤)
       where

 module _
         ((a , p) : Σ a'  A , a'  a')
        where

  -- Bezem, Buchholtz, Grayson
  BBG : (X : Tℤ⁻)  𝓤 ̇
  BBG (X , f) = Σ a'  A , Σ h  (X  a  a') , ((x : X)  h (f x)  p  h x)

  BBG-base : 𝓤 ̇
  BBG-base = BBG ( , succ-ℤ)

  BBG-base-is-singleton : is-singleton BBG-base
  BBG-base-is-singleton = equiv-to-singleton ϕ (singleton-types-are-singletons a)
   where
    ϕ : BBG-base  singleton-type a
    ϕ = Σ-cong ψ
     where
      ψ : (a' : A)
         (Σ h  (  a  a') , ((z : )  h (succ-ℤ z)  p  h z))
         (a  a')
      ψ a' = ℤ-symmetric-induction (lower-funext 𝓤 𝓤 fe)  _  a  a')  _  g)
       where
        g : (a  a')  (a  a')
        g = ((p ∙_) , ∙-is-equiv-left p)

  abstract
   BBG-is-singleton : ((X , f , _) : Tℤ)  is-singleton (BBG (X , f))
   BBG-is-singleton = Tℤ-prop-induction  _  being-singleton-is-prop fe)
                                        BBG-base-is-singleton

  Tℤ-rec : Tℤ  A
  Tℤ-rec X = pr₁ (center (BBG-is-singleton X))

\end{code}

The corresponding computation rule is a bit more work.

\begin{code}

  Tℤ-rec-lemma₁ : (X : Tℤ)  ( X )  a  Tℤ-rec X
  Tℤ-rec-lemma₁ X = pr₁ (pr₂ (center (BBG-is-singleton X)))

  Tℤ-rec-lemma₂ : (X : Tℤ) (x :  X )
                 Tℤ-rec-lemma₁ X ( X ⟩₂ x)  p  Tℤ-rec-lemma₁ X x
  Tℤ-rec-lemma₂ X = pr₂ (pr₂ (center (BBG-is-singleton X)))

  ap-Tℤ-rec-lemma : {X Y : Tℤ} (e : X  Y) (x :  X )
                   ap Tℤ-rec e
                   (Tℤ-rec-lemma₁ X x) ⁻¹
                     (Tℤ-rec-lemma₁ Y ( idtoeq  X   Y  (ap ⟨_⟩ e)  x))
  ap-Tℤ-rec-lemma {X} {Y} refl x =
   ap Tℤ-rec refl                                     =⟨ refl 
   refl                                               =⟨ γ    
   (t X x) ⁻¹  (t X x)                               =⟨ refl 
   (t X x) ⁻¹  (t X ( idtoeq  X   Y  refl  x)) 
    where
     t : (W : Tℤ)   W   a  Tℤ-rec W
     t = Tℤ-rec-lemma₁
     γ = (left-inverse (t X x)) ⁻¹

  ap-Tℤ-rec-loop-lemma₁ : ap Tℤ-rec loop
                         (Tℤ-rec-lemma₁ base 𝟎) ⁻¹  p  Tℤ-rec-lemma₁ base 𝟎
  ap-Tℤ-rec-loop-lemma₁ =
   ap Tℤ-rec loop                                            =⟨ I   
   (t base 𝟎) ⁻¹  (t base ( idtoeq   (ap ⟨_⟩ loop)  𝟎)) =⟨ II  
   (t base 𝟎) ⁻¹  (t base (succ-ℤ 𝟎))                       =⟨ III 
   (t base 𝟎) ⁻¹  (p  t base 𝟎)                            =⟨ IV  
   (t base 𝟎) ⁻¹  p  t base 𝟎                              
    where
     t : (X : Tℤ)   X   a  Tℤ-rec X
     t = Tℤ-rec-lemma₁
     I   = ap-Tℤ-rec-lemma loop 𝟎
     III = ap  -  (t base 𝟎) ⁻¹  -) (Tℤ-rec-lemma₂ base 𝟎)
     IV  = ∙assoc (t base 𝟎 ⁻¹) p (t base 𝟎) ⁻¹
     II  = ap  -  (t base 𝟎) ⁻¹  (t base ( -  𝟎))) γ
      where
       γ : idtoeq   (ap ⟨_⟩ loop)  succ-ℤ-≃
       γ =  idtoeq   (ap ⟨_⟩ loop)                        =⟨ I'   
            (pr₁ (ϕ loop)       , pr₁ (pr₂ (ϕ loop)))       =⟨ refl 
            (pr₁ (ϕ (ψ loop-≅)) , pr₁ (pr₂ (ϕ (ψ loop-≅)))) =⟨ II'  
            (pr₁ loop-≅         , pr₁ (pr₂ loop-≅))         
             where
              ϕ : base  base  base  base
              ϕ =  characterization-of-Tℤ-= base base 
              ψ : base  base  base  base
              ψ =  characterization-of-Tℤ-= base base ⌝⁻¹
              I' = h loop
               where
                h : {X Y : Tℤ} (p : X  Y)
                      idtoeq  X   Y  (ap ⟨_⟩ p)
                      (pr₁ (  characterization-of-Tℤ-= X Y  p) ,
                        pr₁ (pr₂ ( characterization-of-Tℤ-= X Y  p)))
                h refl = refl
              II' = ap  -  (pr₁ - , pr₁ (pr₂ -))) (ε loop-≅)
               where
                ε : ϕ  ψ  id
                ε = inverses-are-sections ϕ
                     (⌜⌝-is-equiv (characterization-of-Tℤ-= base base))

  ap-Tℤ-rec-loop-lemma₂ : ap Tℤ-rec loop
                         transport  -  -  -) (Tℤ-rec-lemma₁ base 𝟎) p
  ap-Tℤ-rec-loop-lemma₂ =
   ap Tℤ-rec loop                                       =⟨ I  
   (Tℤ-rec-lemma₁ base 𝟎) ⁻¹  p  Tℤ-rec-lemma₁ base 𝟎 =⟨ II 
   transport  -  -  -) (Tℤ-rec-lemma₁ base 𝟎) p     
    where
     I  = ap-Tℤ-rec-loop-lemma₁
     II = (transport-along-= (Tℤ-rec-lemma₁ base 𝟎) p) ⁻¹

  Tℤ-rec-comp : (Tℤ-rec base , ap Tℤ-rec loop)  (a , p)
  Tℤ-rec-comp = (to-Σ-= ((Tℤ-rec-lemma₁ base 𝟎) , (ap-Tℤ-rec-loop-lemma₂ ⁻¹))) ⁻¹

\end{code}

Now we will deviate from Bezem et al. a bit by deriving the universal property
rather than the induction principle. The proof of the universal property uses
lemmas and techniques from Section 4.2 of the paper by Bezem et al.

Above we constructed a map of type Tℤ → A, namely Tℤ-rec using the BBG-type. In
what follows we take the reverse route: we start with a map f : Tℤ → A and then
construct something in the BBG-type so that f and Tℤ-rec coincide.

First some general lemmas.

\begin{code}

≅-comp-Tℤ : (X Y Z : Tℤ)  X  Y  Y  Z  X  Z
≅-comp-Tℤ X Y Z (e , i , c) (e' , i' , c') =
 (e'  e , ∘-is-equiv-abstract i i' , ψ)
  where
   abstract
    ψ : e'  e   X ⟩₂   Z ⟩₂  e'  e
    ψ = dfunext fe₀ γ
     where
      γ : e'  e   X ⟩₂   Z ⟩₂  e'  e
      γ x = e' (e ( X ⟩₂ x)) =⟨ ap e' (happly c x) 
            e' ( Y ⟩₂ (e x)) =⟨ happly c' (e x) 
             Z ⟩₂ (e' (e x)) 

to-=-of-≅ : (X Y : Tℤ) {f g : X  Y}
           pr₁ f  pr₁ g
           f  g
to-=-of-≅ X Y h =
 to-subtype-=
   f'  ×-is-prop (being-equiv-is-prop' fe₀ fe₀ fe₀ fe₀ f')
         (equiv-to-prop (≃-funext fe₀ _ _)
          (Π-is-prop fe₀  _  ⟨⟩-is-set Y))))
  (dfunext fe₀ h)

to-Tℤ-=-comp : (X Y Z : Tℤ) (f : X  Y) (g : Y  Z)
              to-Tℤ-= X Z (≅-comp-Tℤ X Y Z f g)
              to-Tℤ-= X Y f  to-Tℤ-= Y Z g
to-Tℤ-=-comp X Y Z f g =
 ϕ X Z (≅-comp-Tℤ X Y Z f g)                 =⟨ I    
 ϕ X Z (ψ X Z (p  q))                       =⟨ II   
 p  q                                       =⟨ refl 
 ϕ X Y f  ϕ Y Z g                           
  where
   ϕ : (X Y : Tℤ)  X  Y  X  Y
   ϕ = to-Tℤ-=
   ψ : (X Y : Tℤ)  X  Y  X  Y
   ψ X Y =  characterization-of-Tℤ-= X Y 
   p : X  Y
   p = ϕ X Y f
   q : Y  Z
   q = ϕ Y Z g
   II = η X Z (p  q)
    where
     η : (X Y : Tℤ)  ϕ X Y  ψ X Y  id
     η X Y = inverses-are-retractions (ψ X Y)
              (⌜⌝-is-equiv (characterization-of-Tℤ-= X Y))
   I = ap (ϕ X Z) γ

\end{code}

    The proof below is done with to-=-of-≅ (rather than directly) for
    type-checking efficiency reasons.

\begin{code}

    where
     γ = ≅-comp-Tℤ X Y Z f g                 =⟨ to-=-of-≅ X Z w      
         ≅-comp-Tℤ X Y Z (ψ X Y p) (ψ Y Z q) =⟨ (lemma X Y Z p q) ⁻¹ 
         ψ X Z (p  q)                       
      where
       lemma : (X Y Z : Tℤ) (p : X  Y) (q : Y  Z)
              ψ X Z (p  q)  ≅-comp-Tℤ X Y Z (ψ X Y p) (ψ Y Z q)
       lemma X Y Z refl refl = to-=-of-≅ X Z  x  refl)
       w : pr₁ g  pr₁ f  pr₁ (ψ Y Z (to-Tℤ-= Y Z g))  pr₁ (ψ X Y p)
       w x = v (pr₁ f x)  ap (pr₁ (ψ Y Z q)) (u x)
        where
         ε : (X Y : Tℤ)  ψ X Y  ϕ X Y  id
         ε X Y = inverses-are-sections (ψ X Y)
                  (⌜⌝-is-equiv (characterization-of-Tℤ-= X Y))
         u : pr₁ f  pr₁ (ψ X Y p)
         u = happly (ap pr₁ ((ε X Y f) ⁻¹))
         v : pr₁ g  pr₁ (ψ Y Z q)
         v = happly (ap pr₁ ((ε Y Z g) ⁻¹))

\end{code}

Now some constructions for the BBG-type. The map Tℤ-action appears in Lemma 4.6
of Bezem et al.

\begin{code}

Tℤ-action : (X : Tℤ)   X      X 
Tℤ-action X x 𝟎       = x
Tℤ-action X x (pos n) = ( X ⟩₂   ^ (succ n)) x
Tℤ-action X x (neg n) = ( X ⟩₂⁻¹ ^ (succ n)) x

Tℤ-action-commutes-with-⟨⟩₂ : (X : Tℤ) (x :  X )
                             Tℤ-action X ( X ⟩₂ x)
                              X ⟩₂  Tℤ-action X x
Tℤ-action-commutes-with-⟨⟩₂ X x 𝟎       = refl
Tℤ-action-commutes-with-⟨⟩₂ X x (pos n) =
 ap  X ⟩₂ ((commute-with-iterated-function  X ⟩₂  X ⟩₂  _  refl) n x) ⁻¹)
Tℤ-action-commutes-with-⟨⟩₂ X x (neg n) = γ
 where
  γ : ( X ⟩₂⁻¹ ^ (succ n)) ( X ⟩₂ x)   X ⟩₂ (( X ⟩₂⁻¹ ^ (succ n)) x)
  γ = (commute-with-iterated-function  X ⟩₂  X ⟩₂⁻¹ ϕ (succ n) x) ⁻¹
   where
    ϕ :  X ⟩₂   X ⟩₂⁻¹   X ⟩₂⁻¹   X ⟩₂
    ϕ y =  X ⟩₂ ( X ⟩₂⁻¹ y) =⟨ I  
          y                   =⟨ II 
           X ⟩₂⁻¹ ( X ⟩₂ y) 
     where
      I  = inverses-are-sections  X ⟩₂ (⟨⟩₂-is-equiv X) y
      II = (inverses-are-retractions  X ⟩₂ (⟨⟩₂-is-equiv X) y) ⁻¹

Tℤ-action-commutes-with-⟨⟩₂-= : (X : Tℤ) (x :  X )
                               Tℤ-action X ( X ⟩₂ x)   X ⟩₂  Tℤ-action X x
Tℤ-action-commutes-with-⟨⟩₂-= X x = dfunext fe₀ (Tℤ-action-commutes-with-⟨⟩₂ X x)

Tℤ-action-base-is-shift : (x : )  Tℤ-action base x   y  y +ℤ x)
Tℤ-action-base-is-shift x 𝟎       = refl
Tℤ-action-base-is-shift x (pos n) = refl
Tℤ-action-base-is-shift x (neg n) = happly (ap (_^ succ n) (ap ⌜_⌝⁻¹ ϕ)) x
 where
  ϕ :  base ⟩₂-≃  succ-ℤ-≃
  ϕ = to-subtype-= (being-equiv-is-prop' fe₀ fe₀ fe₀ fe₀) refl

Tℤ-action-is-equiv : (X : Tℤ) (x :  X )  is-equiv (Tℤ-action X x)
Tℤ-action-is-equiv =
 Tℤ-prop-induction  X  Π-is-prop fe₀
                    x  being-equiv-is-prop' fe₀ fe₀ fe₀ fe₀ (Tℤ-action X x)))
                   γ
  where
   γ : (x : )  is-equiv (Tℤ-action base x)
   γ x = equiv-closed-under-∼  y  y +ℤ x) (Tℤ-action base x)
          (+ℤ-is-equiv-right x) (Tℤ-action-base-is-shift x)

Tℤ-action-is-Tℤ-map : (X : Tℤ) (x :  X )
                     (Tℤ-action X x  succ-ℤ   X ⟩₂  Tℤ-action X x)
Tℤ-action-is-Tℤ-map = Tℤ-prop-induction i γ
 where
  i : (X : Tℤ)
     is-prop ((x :  X )  (Tℤ-action X x  succ-ℤ   X ⟩₂  Tℤ-action X x))
  i X = Π-is-prop fe₀
          x  equiv-to-prop
                 (≃-funext fe₀ (Tℤ-action X x  succ-ℤ) ( X ⟩₂  Tℤ-action X x))
                 (Π-is-prop fe₀  _  ⟨⟩-is-set X)))
  γ : (x : )
      Tℤ-action base x  succ-ℤ  succ-ℤ  Tℤ-action base x
  γ x = dfunext fe₀ h
   where
    h : Tℤ-action base x  succ-ℤ  succ-ℤ  Tℤ-action base x
    h y = Tℤ-action base x (succ-ℤ y) =⟨ I   
          (succ-ℤ y) +ℤ x             =⟨ II  
          succ-ℤ (y +ℤ x)             =⟨ III 
          succ-ℤ (Tℤ-action base x y) 
     where
      I   = Tℤ-action-base-is-shift x (succ-ℤ y)
      II  = right-shift-commutes-with-succ-ℤ x y
      III = ap succ-ℤ ((Tℤ-action-base-is-shift x y) ⁻¹)

Tℤ-action-≅ : (X : Tℤ) (x :  X )  base  X
Tℤ-action-≅ X x =
 (Tℤ-action X x , Tℤ-action-is-equiv X x , Tℤ-action-is-Tℤ-map X x)

Tℤ-action-= : (X : Tℤ) (x :  X )  base  X
Tℤ-action-= X x = to-Tℤ-= base X (Tℤ-action-≅ X x)

Tℤ-action-lemma : (X : Tℤ) (x :  X )
                 Tℤ-action X ( X ⟩₂ x)
                 Tℤ-action X x  succ-ℤ
Tℤ-action-lemma X x = Tℤ-action-commutes-with-⟨⟩₂-= X x
                     (Tℤ-action-is-Tℤ-map X x) ⁻¹

Tℤ-action-=-lemma : (X : Tℤ) (x :  X )
                   Tℤ-action-= X ( X ⟩₂ x)  loop  Tℤ-action-= X x
Tℤ-action-=-lemma X x =
 Tℤ-action-= X ( X ⟩₂ x)                                        =⟨ refl 
 to-Tℤ-= base X (Tℤ-action-≅ X ( X ⟩₂ x))                       =⟨ I    
 to-Tℤ-= base X (≅-comp-Tℤ base base X loop-≅ (Tℤ-action-≅ X x)) =⟨ II   
 to-Tℤ-= base base loop-≅  to-Tℤ-= base X (Tℤ-action-≅ X x)     =⟨ refl 
 loop  Tℤ-action-= X x                                          
  where
   I  = ap (to-Tℤ-= base X) ϕ
    where
     ϕ = to-=-of-≅ base X (happly (Tℤ-action-lemma X x))
   II = to-Tℤ-=-comp base base X loop-≅ (Tℤ-action-≅ X x)

\end{code}

Finally, as promised, every map r : Tℤ → A gives rise to an element of the
BBG-type so that r and Tℤ-rec coincide.

\begin{code}

module _
        {A : 𝓤 ̇ }
        (r : Tℤ  A)
       where

 BBG-map : (X : Tℤ)   X   r base  r X
 BBG-map X x = ap r (Tℤ-action-= X x)

 BBG-map-lemma : (X : Tℤ) (x :  X )
                BBG-map X ( X ⟩₂ x)  ap r loop  BBG-map X x
 BBG-map-lemma X x = BBG-map X ( X ⟩₂ x)                      =⟨ refl 
                     ap r (Tℤ-action-= X ( X ⟩₂ x))           =⟨ I    
                     ap r (loop  Tℤ-action-= X x)             =⟨ II   
                     ap r loop  ap r (Tℤ-action-= X x)        =⟨ refl 
                     ap r loop  BBG-map X x                   
  where
   I  = ap (ap r) (Tℤ-action-=-lemma X x)
   II = ap-∙ r loop (Tℤ-action-= X x)

 module _
         (fe : funext 𝓤 𝓤)
        where

  open Tℤ-rec {𝓤} {A} fe

  ∼-to-Tℤ-rec : r  Tℤ-rec (r base , ap r loop)
  ∼-to-Tℤ-rec X = ap pr₁ e
   where
    b₁ : BBG (r base , ap r loop) (X )
    b₁ = (r X , BBG-map X , BBG-map-lemma X)
    b₂ : BBG (r base , ap r loop) (X )
    b₂ = center (BBG-is-singleton (r base , ap r loop) X)
    e : b₁  b₂
    e = singletons-are-props (BBG-is-singleton (r base , ap r loop) X) b₁ b₂

\end{code}

But the above gives us the uniqueness principle for 𝕊¹ (Lemma 6.2.8 in the HoTT
Book) which says that any two maps f,g : 𝕊¹ → A that agree on base and loop must
coincide. Combined with the recursion principle, this quickly gives us the
universal property.

\begin{code}

Tℤ-universal-map : (A : 𝓤 ̇ )  (Tℤ  A)  Σ a  A , a  a
Tℤ-universal-map A f = (f base , ap f loop)

Tℤ-universal-property : FunExt
                       (A : 𝓤 ̇ )
                       is-equiv (Tℤ-universal-map A)
Tℤ-universal-property {𝓤} fe A = qinvs-are-equivs ϕ (ψ , η , ε)
 where
  open Tℤ-rec {𝓤} {A} (fe 𝓤 𝓤)
  ϕ : (Tℤ  A)  (Σ a  A , a  a)
  ϕ f = (f base , ap f loop)
  ψ : (Σ a  A , a  a)  (Tℤ  A)
  ψ (a , p) = Tℤ-rec (a , p)
  η : ψ  ϕ  id
  η f = dfunext (fe 𝓤₁ 𝓤)  X  ∼-to-Tℤ-rec f (fe 𝓤 𝓤) X ⁻¹)
  ε : ϕ  ψ  id
  ε = Tℤ-rec-comp

\end{code}

Finally, we use our abstract proof that the universal property implies induction
(which is developed separately in CircleInduction) to derive the induction
principle.

\begin{code}

open import Circle.Induction

module _
        (fe : FunExt)
        (A : Tℤ  𝓤 ̇ )
        (a : A base)
        (l : transport A loop a  a)
       where

 open 𝕊¹-induction Tℤ base loop (Tℤ-universal-property fe) A a l

 Tℤ-induction : (x : Tℤ)  A x
 Tℤ-induction = 𝕊¹-induction

 Tℤ-induction-comp : (Tℤ-induction base , apd Tℤ-induction loop)
                   =[ Σ y  A base , transport A loop y  y ] (a , l)
 Tℤ-induction-comp = 𝕊¹-induction-comp
                      (equiv-to-set loops-at-base-equivalent-to-ℤ ℤ-is-set)

\end{code}